JESD 2021
DOI: 10.7176/jesd/12-8-04
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Minimum Wages on Inflation and Unemployment in East Java - Indonesia

Abstract: Unemployment and inflation are two macroeconomic problems that have a trade-off, this means that the relationship between inflation and unemployment is negative and the relationship is also called the Phillips curve. The increase in the minimum wage is one of the causes of inflation and unemployment. This study aims to determine the relationship between minimum wage and inflation, the relationship between minimum wage and unemployment, the relationship between inflation and unemployment. This study uses panel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…The results of this study support the results of previous research conducted by Brouillette et al (2017), which suggested that an increase in the minimum wage can contribute to higher inflation rates. However, it is essential to note that the results of this study contradict the research conducted by Suparta et al (2021). In Suparta et al (2021) research, the independent variable is only the minimum wage.…”
Section: Resultscontrasting
confidence: 73%
See 3 more Smart Citations
“…The results of this study support the results of previous research conducted by Brouillette et al (2017), which suggested that an increase in the minimum wage can contribute to higher inflation rates. However, it is essential to note that the results of this study contradict the research conducted by Suparta et al (2021). In Suparta et al (2021) research, the independent variable is only the minimum wage.…”
Section: Resultscontrasting
confidence: 73%
“…However, it is essential to note that the results of this study contradict the research conducted by Suparta et al (2021). In Suparta et al (2021) research, the independent variable is only the minimum wage. In this study, three independent variables were added so that the number became four variables independent, but the effect of the minimum wage on inflation is positive and insignificant.…”
Section: Resultscontrasting
confidence: 73%
See 2 more Smart Citations